KONTRIBUSI RESISTANCE TO CHANGE TERHADAP WORK ENGAGEMENT PADA KARYAWAN PT.GANESHA OPERATION - Dhia Andriani (Jurnal Riset Psikologi, 2018)
Abstract: Contribution of resistance to change to work engagement on the employees of the PT.Ganesha Operation Bukittinggi.This study aims to see the contribution of resistance to change to work engagement on employees of PT. Ganesha Operation Bukittinggi. This research was analyzed using Simple Linear Regression Analysis technique assisted by SPSS 16.0 for windows software. The research population is employees of PT. Ganesha Operation Bukittinggi with a sample of 30 subjects with Purposive Sampling technique. Based on the hypothesis test, it is found that the value of F= 57,891 and p=0,000 (p<0,01) so that the equation y=159,802 - 0,930X can be used as prediction of contribution of resistance to change to work engagement. Besides, R2=0,674 were obtained, so the result showed that there is contribution of resistance to change to work engagement on PT. Ganesha Operation Bukittinggi.Keywords: Resistance to change, work engagement, employees of the PT.Ganesha Operation BukittinggiAbstrak: Kontribusi resistance to change terhadap work engagement pada karyawan PT.Ganesha Operation Bukittinggi.Penelitian ini bertujuan untuk melihat kontribusi resistance to change terhadap work engagement pada karyawan PT. Ganesha Operation Bukittinggi. Penelitian ini dianalisis menggunakan teknik Statistik Analisis Regresi Linear Sederhana yang dibantu dengan perangkat lunak SPSS16.0 for windows. Populasi penelitian yaitu karyawan PT. Ganesha Operation Bukittinggi dengan sampel sebanyak 30subjek dengan teknik Sampling Purposive. Berdasarkan uji hipotesis maka didapatkan didapatkan nilai F=57,891 dan p=0,000 (p<0,01) sehingga persamaan y=159,802– 0,930X dapat digunakan sebagai prediksi kontribusi resistance to change terhadap work engagement. Selain itu diperoleh nilai R2 = 0,674 sehingga hasil penelitian menunjukkan bahwa terdapat kontribusi resistance to change terhadap work engagement pada karyawan PT. Ganesha Operation Bukittinggi.Kata kunci:Resistance to change, work engagement, karyawan PT.Ganesha Operation Bukittinggi